Clinical significance of granule‐containing myeloma cells in patients with newly diagnosed multiple myeloma. (13th October 2016) - Suzuki, Kazuhito; Yano, Shingo; Nishiwaki, Kaichi; Sano, Koji; Shimada, Takaki; Yahagi, Yuichi; Ogasawara, Yoji; Sugiyama, Katsuki; Takahara, Shinobu; Saito, Takeshi; Kasama, Kinuyo; Minami, Jiro; et al.
Abstract: The clinical features and prognostic significance of myeloma cells containing granules remain unclear. The purpose of this retrospective study was to investigate the clinical significance of granule‐containing myeloma cells in patients with newly diagnosed multiple myeloma (NDMM). We retrospectively analyzed the records of 122 patients diagnosed with NDMM between January 2007 and December 2013. Granule‐containing myeloma cells were defined as myeloma cells that exhibited three or more granules in their cytoplasm by May‐Giemsa staining. The patients were classified into two groups, the granule‐containing myeloma (GM) and nongranule‐containing myeloma (non‐GM) groups, depending on the proportion of myeloma cells that contained granules (cut‐off value: 10%). There were 25 (20.5%) patients in the GM group. Patients in the GM group displayed significantly higher CD56 and CD49e expression than those in the non‐GM group ( t ‐test, P  =   0.027 and 0.042). None of the patient characteristics differed significantly between the two groups. There was no significant difference in the chemotherapy profiles of the two groups, and the overall response rates of the two groups were similar. During the median follow‐up period of 33.9 months, the overall survival (OS) in the GM group was similar to that in the non‐GM group; 4‐year OS of the GM and non‐GM groups were 78.5% and 51.9%, respectively ( P  =   0.126). We concluded that cases of NDMM involving granule‐containing myeloma cells are not infrequent. Moreover, CD56 and CD49e expression was significantly higher in the presence of myeloma cell populations, and the presence of granules did not affect survival. Abstract : This article is the first report about the clinical features and prognostic significance of myeloma cells containing granules. There were 20.5% of patients in the granule‐containing myeloma group. The patients were classified into two groups depending on the proportion of their myeloma cells that contained granules. The granule‐containing myeloma group displayed significantly higher CD56 and CD49e expression, but did not influence survival.